Humanitarian erudition in the professional competence of the culturologist - V.S. Grytsenko, (Ukrainian Cultural Studies, 2018)
The article is devoted to the study of humanitarian education as a sign of the professionalism of a culturologist. Special attention is paid to the actualization of cultural science as a science capable of influencing the contemporary processes of cultural development, the necessity of taking into account the given factor in the formation of culturological competences. Humanitarian “all-seeing” of cultural studies is considered as the basis to be the dominant of  modern humanities. In the conditions of crisis of self-definition a requirement grows in development of knowledge about a culture, a too – in humanitarian erudition as condition of culturological vision of all. She can be formed due to corresponding protocols of professional preparation of culturologist, procedures of grant to them the necessary knowledge and practical skills, in fact universality of the expected competenses must be commensurable to the calls of modern humanitarian sciences  in their essence understanding. It does actual a question in relation to the value of humanitarian knowledge on the modern stage of development of Man, but culturology, busy at first of all the analysis of spiritual senses, finds out her unique productivity  among  humanitarian  research  projects.  Her  humanitarian  dominant  finds all more confirmations  in  a  scientific  environment that  promotes demand on professional accordance to such her position, that in turn envisages going beyond the scopes of formal set of competenses. Humanitarian erudition eliminates any formalization, in fact all-round form, is charged energy of human development, inflexible in aspiration to the spiritual kernel of culture. Working mainly with empiric facts, real culturologist is at essence level of their understanding, owning wide knowledge about procedures of examinations of the cultural phenomena, criteria of their estimation. A humanitarian awareness allows to hin to be included in the thin sphere of internal man from positions of knowledge of human psyche, typology of the emotional states, methods of questioning, questionnaire, testing, analytical procedures. Among the terms of competence an important place belongs to understanding of heuristic potential of analysis of the art straight related to the essence human kernel in all many-sided nature of his display.